Pediatric Cardiology in The Past, Present, and Future: Its Role in The Prevention and Management of Cardiovascular Disease - Bambang Madiyono (Paediatrica Indonesiana, 1998)
Â The title mentioned above is chosen in a consideration that we are now entering the Second Stage Long-Term Development Plan (or PJP-II), even the Sixth Five-Year Development Plan is being passed in part. This is a stage of quality and productivity improvement of our human resources for the sake of developmental success to achieve a fair and wealthy society based on the Pancasila and the Constitution of 1945. In his presidential speech before the General Meeting of People's Advisory Assembly or MPR on Friday, Aug. 16, 1996, President Soeharto declared that: "The service of public health has been continuously improving. Various efforts in the medical sector has already reduced the infant mortality, increased the life expectancy, reduced the population growth, and improved the quality of other physical and spiritual life."On the other side, cardiovascular disease, according to the Indonesian Household Health Survey of 1996, has become a major problem, with high morbidity and mortality. It is this critical condition that made a starting point to this discussion. I hope that this following discussion can be seen as a contribution in the development of pediatrics, especially in pediatric cardiology, for the benefit of our nation progress in raising the quality of our human resources in order to face the era of globalization.